A Preconditioned Conjugated Gradient Method for Computing Ground States of Rotating Dipolar Bose-Einstein Condensates via Kernel Truncation Method for Dipole-Dipole Interaction Evaluation (Communications in Computational Physics, 2020)
In this paper, we propose an efficient and accurate method to compute theground state of 2D/3D rotating dipolar BEC by incorporating the Kernel TruncationMethod (KTM) for Dipole-Dipole Interaction (DDI) evaluation into the newly-developedPreconditioned Conjugate Gradient (PCG) method [9]. Adaptation details of KTMand PCG, including multidimensional discrete convolution acceleration for KTM, choiceof the preconditioners in PCG, are provided. The performance of our method is confirmed with extensive numerical tests, with emphasis on spectral accuracy of KTM andefficiency of ground state computation with PCG. Application of our method showssome interesting vortex lattice patterns in 2D and 3D respectively.